DynaMed Plus®: An Evidence-Based Clinical Reference Resource. Issue 2 (3rd April 2018) - Charbonneau, Deborah H.; James, LaTeesa N.
ABSTRACT: DynaMed Plus ® from EBSCO Health is an evidence-based tool that health professionals can use to inform clinical care. DynaMed Plus content undergoes a review process, and the evidence is synthesized in detailed topic overviews. A unique three-level rating scale is used to assess the quality of available evidence. Topic overviews summarize current evidence and provide recommendations to support health providers at the point-of-care. Additionally, DynaMed Plus content can be accessed via a desktop computer or mobile platforms. Given this, DynaMed Plus can be a time-saving resource for health providers. Overall, DynaMed Plus provides evidence summaries using an easy-to-read bullet format, and the resource incorporates images, clinical calculators, patient handouts, and practice guidelines in one place.